1585. Bloodstream Infection Survey in High-Risk Oncology Patients (BISHOP) with Fever and Neutropenia (FN): Correlation Between Initial Empiric Antibiotic Regimen Correlation and Susceptibility Patterns. (26th November 2018) - Zimmer, Andrea; Freifeld, Alison G; Arnold, Christopher; Baddley, John W; Chandrasekar, Pranatharthi; El Boghdadly, Zeinab; Gomez, Carlos; Maziarz, Eileen K; Pergam, Steven; Rolston, Kenneth V; Satyanarayana, Gowri; Shoham, Shmuel; et al.
Abstract: Background: The empiric initial antibiotic regimen (IAR) for treatment of febrile neutropenia (FN) relies on a knowledge of epidemiology and susceptibility patterns of bacterial bloodstream infections (BSI), especially in high-risk patient populations, i.e., those receiving chemotherapy for hematologic malignancies (HM) or undergoing hematopoietic stem cell transplant (HCT). As the last US national survey of BSI epidemiology in cancer patients was published in 2003, we sought to update these data focusing exclusively on high-risk patients with attention to IARs used and their concordance with susceptibilities of isolated bloodstream pathogens. Methods: A prospective ongoing survey among 14 high-volume US cancer centers submitting clinical and microbiologic data from consecutive HM patients with BSI during first FN after cytotoxic chemotherapy or HCT. Concordance between antibiotic and BSI was determined by investigator (AZ, AF) interpretation of susceptibility reports provided by each center compared with IAR used, for single organism bacteremias only. Results: Among 294 FN bacteremic episodes (93 HCT), there were 336 bacterial pathogens (48.5% Gram negative [GN] 46.5% Gram positive [GP] and 6% anaerobes), with 88% monomicrobial episodes. E. coli and viridans group Streptococci (VGS) were the most commonly isolated GN and GP, respectively, each accounting for nearly 25% of total organisms identified. IARs included cefepime 61%, piperacillin–tazobactam 24%, and meropenem 8%. Isolates were nonsusceptible to the IAR in 38/227 (17%) of FN episodes. Antibiotic mismatch was more likely to occur with a non-VGS GP (37%) vs. GN (13%) or VGS (2%) P < 0.001. Conclusion: This is the first US national survey of high-risk BSI in FN. Although mismatch between BSI and IAR occurs in 17% of FN bacteremia episodes, this is driven primarily by non-VGS GP isolates such as CoNS and MRSA. Currently used IARs, comprised primarily of cefepime and piperacillin–tazobactam, generally provide reliable coverage for GN isolates across the United States (87%) but careful tracking of this rate is essential to identify further erosion of coverage in the current era of antimicrobial resistance. Disclosures: A. Zimmer, Merck: Investigator, Research grant. A. G. Freifeld, Merck: Investigator, Research grant. S. Pergam, Merck: Consultant, Consulting fee; Chimerix: Consultant, Consulting fee. K. V. Rolston, Merck: Investigator, Research grant; JMI Laboratories: Investigator, Research grant; Shionogi (Japan): Investigator, Research grant. S. Shoham, Merck: Investigator and Scientific Advisor, Consulting fee and Grant recipient; Astellas: Investigator, Grant recipient; Shionogi (Japan): Investigator, Grant recipient; Gilead: Investigator, Grant recipient; Shire: Investigator, Grant recipient. T. J. Walsh, Merck: Grant Investigator, Research grant; Atellas: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research grant; Gilead: Scientific Advisor, Consulting fee; Allergan: Grant Investigator and Scientific Advisor, Consulting fee and Research grant; Scynexis: Grant Investigator, Research grant; Amplyx: Grant Investigator, Research grant; Shionogi: Scientific Advisor, Consulting fee. J. A. Young, GSK: Investigator, The University of Minnesota is reimbursed for contract costs associated with conducting clinical trials of vaccine. I receive no personal financial benefit.. J. Meza, Merck: Investigator, Research grant. Y. Zhang, Merck: Investigator, Research grant.